Implementasi Load Balancing pada Cloud Computing dengan Algoritme Improved Weighted Least Connection - Muhammad Denny Chrisna Pujangga; Nurul Hidayat; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Load balancing is a workload distribution mechanism that is widely used in distributed systems. One of the most widely used load balancing algorithms is the Weighted Least Connection Algorithm. The Weighted Least Connection algorithm has a problem that when a new server is added to the server cluster system when there are many user requests, the Weighted Least Connection algorithm will distribute the workload intensively to the new server, causing an uneven distribution of server workloads. To overcome this problem, the Weighted Least Connection algorithm was developed by combining two algorithms, the Server Selection algorithm and the Overload Reduce algorithm into one algorithm, namely the Improved Weighted Least Connection algorithm. This study applies the Improved Weighted Least Connection algorithm on the cloud architecture using the CloudSim Plus simulator. The results of this study indicate that the distribution of the Weighted Least Connection algorithm task is more even than the Improved Weighted Least Connection algorithm on heavier workloads. Meanwhile, for the difference in the distribution of tasks to VM 3, there is not much difference between the Weighted Least Connection algorithm and the Improved Weighted Least Connection algorithm, with an average of 4.81 tasks per 10 seconds and an average of 28.3% cpu usage for the algorithm. Weighted Least Connection, and an average of 4.75 tasks per 10 seconds and an average of 28.02% cpu usage for the Improved Weighted Least Connection algorithm.